2008
DOI: 10.1159/000109597
|View full text |Cite
|
Sign up to set email alerts
|

Ewing’s Sarcoma as Second Malignant Neoplasm after Retinoblastoma: A Case Report

Abstract: Objectives: To report a case of a child with the hereditary form of unilateral retinoblastoma (RB), who developed Ewing’s sarcoma of the right fibula 3 years after the enucleation of the right eye. Case Presentation and Intervention: The child was diagnosed as a case of RB of the right eye at the age of 9 months. He was fully investigated and found to have locally advanced RB with bone marrow involvement (Reese-Ellsworth stage IVA). Enucleation was recommended to the family, but they refused. The patient recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Previously, six cases of Ewing’s sarcoma in patients with a prior history of bilateral [1, 6, 8, 16] and two cases of unilateral [6, 12] retinoblastoma have been reported. Here, we present a case of a child with unilateral RB who developed Ewing’s sarcoma of the right humerus 2 years after enucleation of the left eye, and a review of the pertinent literature.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, six cases of Ewing’s sarcoma in patients with a prior history of bilateral [1, 6, 8, 16] and two cases of unilateral [6, 12] retinoblastoma have been reported. Here, we present a case of a child with unilateral RB who developed Ewing’s sarcoma of the right humerus 2 years after enucleation of the left eye, and a review of the pertinent literature.…”
Section: Introductionmentioning
confidence: 99%
“…Although Ewing's sarcoma has been recognized as a second cancer in children who have been treated for retinoblastoma, [22][23][24][25] it has not, to our knowledge, been associated with other cancer-predisposition syndromes. 26 We found that six patients with Ewing's sarcoma had pathogenic germline mutations in TP53 (in four patients), PMS2 (in one), or RET (in one), although we cannot state with certainty that each mutation had a bearing on the patient's cancer.…”
Section: Discussionmentioning
confidence: 95%
“…org/ site). These genes were classified into three categories: tumorsuppressor genes (58 genes), 9 tyrosine kinase genes (23), and other cancer genes (395). Our analyses of the genes in these three categories focused on known hotspot-activating mutations in genes encoding kinases and on truncation mutations in genes encoding tumor-suppressor proteins and in other cancer genes.…”
Section: Enrollment Of the Patientsmentioning
confidence: 99%
“…Finally, several authors have reported on the association of Ewing's sarcoma after diagnoses and treatment for retinoblastoma [75, 76]. Spunt et al [42] published on a cohort of 6 Ewing's patients diagnosed after treatment for various cancers including lymphoma, leukemia, Wilms tumor, and retinoblastoma.…”
Section: Search Strategy and Selection Criteriamentioning
confidence: 99%